MORPHOLOGICAL CHANGES IN THE LUNGS OF RATS LIVING UNDER COMPRESSED AIR CONDITIONS - Smith, F. J. C. (The Rockefeller University Press, 1932)
1. The alveolar cells in the lungs of young rats are greater in number and size than in old rats, a gradual transition to the state in the latter occurring from about the 4th to the 6th months of life. 2. On prolonged exposure to an environment having an 83.6 per cent oxygen tension, the cellularity of the alveoli is increased in both young and old animals, so that after 2 to 3 weeks it is impossible to distinguish them by morphological differences. Numerous mitotic figures are present in the alveolar cells. This hyperplasia and hypertrophy is a change which persists for months after the rats return to normal air. 3. Young rats do not develop the symptoms of acute oxygen poisoning, although some perivascular edema and dilatation of the lymphatics results on the 4th day of exposure, when intense acute pulmonary edema is present in old rats. 4. The mortality of acute oxygen poisoning is directly proportional to the age of the animals, although the majority of rats under 6 months of age survive this state and continue in apparent good health for as long as 72 days. All deaths during the acute stage in an 83.6 per cent oxygen tension occur on the 4th day of exposure. 5. After 1 month of exposure lesions are to be seen in the small arterioles of the lungs, consisting of a thickening and hyalinization of the walls with ultimate thrombosis of many. These vascular changes are identical with those seen in the arterioles of the kidney in chronic vascular nephritis. 6. Around the 45th day of exposure the large pulmonary arteries contain lesions in the media. The walls become loose meshed, thickened, and hyalinized, and hyaline cartilage formation is associated with these changes. 7. Reexposure of animals following an interval of 40 days in normal air subsequent to the first exposure of 72 days, does not produce any clinical or pathological changes. An adaptation to this toxic oxygen tension is produced during the first exposure, so that oxygen poisoning does not occur on second exposure. The increased cellularity of the alveolar walls persists. 8. The similarity in the morphological structure of the alveoli in young rats and in previously exposed old rats has a definite relationship to the adaptation that occurs to an oxygen tension of 83.6 per cent, preventing the development of acute oxygen poisoning on reexposure.